Remote Sensing Technology in Entomology - Madhuri, Burjikindi; Bharghavi, Kolli; Supriya, Koosari; Maharaj, Satwika; Yashaswini, Gummudala; Erla, Sravanthi (Chronicle of Bioresource Management, 2020)
Remote sensing is a technology that is used to collect information and examine an object, place, or phenomenon without making any physical contact with it. The spectral behavior of features on the earth is essential in the applications involving remote sensing. These days, it’s a useful tool for managing plant diseases and insect pests on various crops and fruit orchards through forecasting, detection, and control. The primary goals of this use was to reduce the amount of chemical pesticide pollution in the environment and to gather data that aids in decision-making for insect pest management. For controlling insect pests and weed detection, aerial remote sensing has proven to be a helpful and promising technique. In order to minimize pest damage and management expenses, remote sensing can offer quick and precise forecasts of specific insect pests.